Electrochromic properties of PANI/TiO2 nanocomposites - Liu, Jing. (2010)
In recent years, much research has been conducted on polyaniline‟s composites with various inorganic nanoparticles to find applications in electrochromic devices. In order to investigate the electrochromic(EC) properties of polyaniline incorporated with nanocrystalline TiO2 particles, we have successfully synthesized polyaniline/TiO2 nanocomposites by in situ oxidative polymerization in different TiO2 contents.